Screening of cognitive performance in kidney transplant recipients: a mini review - Schietzel, Simeon; Kressig, Reto W.; Huynh-Do, Uyen (Frontiers in Nephrology, 2023)
Why should we screen? Prevalence of cognitive impairment in kidney transplant recipients (KTRs) is up to 58%. 10 years graft-loss and mortality rates are above 30 and 50%, and executive malfunctioning increases disadvantageous outcomes.Strong risk factors are older age and chronic kidney disease. However, causes are multifactorial including cardio-and cerebrovascular, neurodegenerative, inflammatory, uremic, psychiatric and lifestyle-related susceptibilities.How should we screen? KTRs specific validated instruments or strategies do not exist. Central element should be a multi-domain cognitive screening test that is sensitive to mild cognitive impairment, corrects for age and education and includes executive functions testing. Cognitive trajectories, affection of everyday-life and psychiatric co-morbidities should be assessed integrating patients` knowledgeable informants.When should we screen? Screening should not be postponed if there is suspicion of impaired cognition. Different time-points after transplantation tend to have their own characteristics.Who should screen? Screening should not be limited to specialists. It can be performed by healthcare professionals after limited amount of training.What are the benefits of screening? Screening does not provide a diagnosis. However, suggestive results change care in multiple ways. Professional dementia work-up should be initiated, adherence secured, complications anticipated (delirium, falls, frailty, functional impairment, malnutrition, etc.), behavioral disorders mitigated, diagnostic and therapeutic "load" adjusted, care-taker burden reduced and changing needs met.We summarize data on prevalence, risk factors and sequelae of cognitive impairment in KTRs. We discuss requirements for appropriate screening strategies and provide guiding principles regarding appropriate and safe care.